DEVELOPMENT OF PISED MEDIA BASED ON REALISTIC MATHEMATICS EDUCATION IN ELEMENTARY SCHOOL - Endro Siswantoro; Abi Suwito (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2021)
Fractions subject is one of the mathematics subjects studied by grade VI elementary school students. The subject is generally still considered difficult by most students. It is known that there are still students who make mistakes in addition and subtraction operations, especially in the fractional subjects. In addition, students also experience conceptual errors when working. In this regard, learning media based on realistic mathematics education is needed. This development research method consists of 9 stages are (1) identification of potential problems, (2) data collection, (3) product design, (4) media design validation, (5) media design revision (stage I), (6) small group trial of media products, (7) product revision (stage II), (8) large group trial, and (9) product revision (stage III). Based on the development results, it was found that PISED media can be made and used easily by relying on straws. The learning media has been tested and obtained a valid and feasible category for use.